Legal Protection Instruments and Fulfilment of Children's Rights as Victims of Domestic Violence Within National Regulations in Indonesia - Hanafi Hanafi (Scholar Center, 2024)
Violence against children is a significant social issue in Indonesia, with its incidence continually rising, signaling a concerning trend. The impacts of such violence are not limited to physical harm but also affect children’s psychological and social well-being, influencing their future development. To address this, it is crucial to strengthen efforts in protecting and fulfilling the rights of children who are victims of violence, particularly through legal frameworks. This research employs a normative legal method, focusing on library studies that analyze legal theories and applicable laws and regulations. The approach is based on a statutory method, complemented by a conceptual approach. The study’s findings indicate that the protection of children who are victims of domestic violence is governed by various national legal provisions. These provisions are primarily found in the 1945 Constitution of the Republic of Indonesia, with specific regulations in Law Number 23 of 2002 on Child Protection, later amended by Law Number 35 of 2014, and Law Number 17 of 2016, which enacts the Government Regulation in Lieu of Law Number 1 of 2016, amending Law Number 23 of 2002. This is further supported by Government Regulation Number 78 of 2021, which addresses Special Protection for Children. These legal instruments highlight the state's commitment to upholding human rights and ensuring the protection of children’s rights. However, to optimize their implementation, it is essential to strengthen related institutions and involve multiple stakeholders, including community support.